Research brief: Analysis of policy responses to seed, fertilizer, food and fuel shocks in three African Regional Economic Communities - Lokosang, L.B.; Kirui, L.K.; Maru, J.; Karugia, Joseph T.; Bahta, Sirak T.; Enahoro, Dolapo K. (2024)
The COVID-19 pandemic and the ongoing Russia-Ukraine war had severe implications for global food security and nutrition. It was feared that food systems would be impacted negatively, especially food, seed, fertilizer, and fuel quantities required for agricultural production. The study aimed to ascertain the extent to which calls to action by AU policy organs, as well as recommendations by experts, to mitigate possible effects of the COVID-19 pandemic, were implemented at the national level across three of the five regional economic communities and whether they yielded any tangible impacts. The study conducted a desk review of literature and key informant interviews in 18 African countries. We found a wide range of varia-tions in terms of country responses to the pan-demic. Countries in the East African Community focused more on expanding targeted social protec-tion programs, Economic Community of West African States countries focused more on support-ing smallholder farmers and digital agriculture, and the Southern African Development Community focused on budgetary stimulus packages. We found a lack of coherence in responding to the crisis within each region to improve the supply and dis-tribution of food, seed, fertilizer, and fuel; thus, necessitating an immediate and aggressive imple-mentation of strategies aligned with continental and regional policy resolutions and recommenda-tions.